Effectiveness of virtual reality in pain management, range of motion and functional performance in frozen shoulder patients: a systematic review - Qazi, Anum Fatima; Asif, Aqsa; Fayyaz, Bisma; Naheed, Summan; Shabbir, Rida; Naqvi, Syed Muhammad Shabbir Ali (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the effectiveness of virtual reality in improving pain management, range of motion and functional performance among frozen shoulder patients. Method: The systematic review was conducted at Khyber Medical University Peshawar between February 2023 - November 2023 and comprised literature search regardless of the year of publication across multiple databases, including Medline via Ovid, Cochrane Library and Physiotherapy Evidence Database, and Google Scholar search engine. Covidence software was used to screen titles, headings and abstracts from the retrieved articles. Experimental trials comparing virtual reality with any other intervention or no intervention with diagnosed cases of frozen shoulder, either unilateral or bilateral, among patients aged >20 years, were included in the systematic review. The risk of bias was evaluated through the Cochrane risk of bias checklist. Results: Of the 8,616 studies, 4(0.04%) were identified by Medline, 7,696(89.32%) by Cochrane Library, 0(0%) by Physiotherapy Evidence Database and 916(10.63%) by Google Scholar. Overall, 31(0.36%) studies were retrieved for full-text review, and, of them, 7(22.6%) were reviewed in detail; 3(42.85%) randomised controlled trials (level of evidence: 2), 2(28.57%) quasi-experimental studies (level of evidence: 3), and 2(28.57%) experimental studies (level of evidence: 3). Conclusion: Virtual reality was found to be a promising intervention for rehabilitating patients with frozen shoulder. Evidence indicated potential improvements in joint range, pain and functional mobility, although findings were mixed, and the quality of evidence was variable. Key Words: Frozen shoulder, Virtual reality, Pain management, Range of motion, Rehabilitation.